Characteristics of Medical Professional Liability Claims in Pediatric Orthopedics. Issue 8 (December 2021) - Burns, Jessica; Shrader, M. Wade; Boan, Carla; Belthur, Mohan
Abstract : Objectives: Medical malpractice is burdensome to the U.S. healthcare system. The following is an epidemiological analysis of the closed medical professional liability (MPL) claims in pediatric orthopedics using data maintained by the Physician Insurers Association of America. Methods: The Physician Insurers Association of America registry of MPL claims from 1985 to 2013 for all specialties included 286, 021 closed claims in the United States. All closed MPL claims for orthopedic surgery in patients younger than 18 years were retrospectively reviewed (N = 2, 671). The error categories, result of the claim, the most common procedures, severity of injury, and the most common presenting and resultant medical conditions were reported with the paid-to-close ratios, average indemnity payment, and average cost of litigation. The pediatric orthopedic population was compared with all orthopedics. The data were adjusted for inflation and trended for the 29-year period. Results: Of the 2671 pediatric orthopedic claims, 881 resulted in a payment and the average indemnity was U.S. $317, 574 with adjustment for inflation - significantly higher than for all of orthopedics at U.S. $268, 817 ( P = 0.0013). The paid-to-close ratio was 33.0%, compared with 28.7% for all of orthopedics ( P = 0.023). Conclusions: Costs to defend individual medical malpractice claims and the average indemnity payment per claim have both increased over time, and pediatric (versus adult) orthopedic claims are more likely to result in payment and result in a higher payment. Knowledge of the details of liability claims should assist practicing general and pediatric orthopedic surgeons in improving patient safety and quality of care, reducing patient injury, and reducing the incidence of MPL claims.